(untitled) (The Proceedings of The International Conference on Climate Change, 2019)
Quality of coastal surface and groundwater is deteriorating day-by-day due to the combined effects of climate change and unwise activities of coastal people. Total Dissolved Solids (TDS) is an important water quality parameter that can be monitored regularly more conveniently by remote sensing techniques. This study aims to evaluate the applicability of Landsat 8 OLI images to detect TDS of surface water of coastal Bangladesh. It employs 14 different band compositions to compute an equation through multiple regression analysis among the band values and 18 sample TDS values collected from field visit in the last week of November 2018. Level 2 product of Landsat 8 OLI image (path/row: 138/44) dated 27 November 2018 has been used for the analysis. A regression equation has been computed with the bands Blue, Green and Red, which can predict TDS (mg/L) 83.6% correctly. Analysis of change detection study revealed that water areas with TDS level 100 – 600 mg/L have been reduced 28.9% and water areas with unacceptable TDS level (>1200 mg/L) have been increased 32.7% between 2014 and 2018. Contamination of surface waters has led to freshwater scarcity and health hazard for the coastal people.